METHODOLOGICAL PRINCIPLES OF COORDINATION OF ADVANCED EDUCATIONAL METHODOLOGY - Sattorov Sardorbek (American Journals, 2023)
The current state of the education system is characterized by the increasing role of non-traditional educational technologies. Changing knowledge on the part of the learner with their help is much faster than traditional technologies. These technologies change the nature of knowledge development, acquisition and distribution, deepening and expanding the content of the studied subject, quickly updating it, using more effective teaching methods, and significantly expanding the opportunity for education for everyone.
Keywords: Advanced education, non-traditional, pedagogical technology, educational process, interactive, educational methodology.